EXTREME CHEMICAL HETEROGENEITY OF GRANITE-DERIVED HYDROTHERMAL FLUIDS: AN EXAMPLE FROM INCLUSIONS IN A SINGLE CRYSTAL OF MIAROLITIC QUARTZ - Kamenetsky V.S.; van Achterbergh E.; Ryan C.G.; Naumov V.B.; Mernagh T.P.; Davidson P. (My University, 2002)
Magma-derived fluids are important in geologic processes (e.g., metal sequestration and ore deposition) but are intrinsically transient. Samples of magmatic fluids represented by fluid inclusions in a single zoned quartz crystal from a miarolitic cavity within a porphyritic leucogranite hosting the Industrialnoe tin deposit, northeastern Russia, were studied by using modern in situ analytical methods (laser Raman spectroscopy, proton-induced X-ray emission). The fluid inclusions are either dominated by vapor or by complex multiphase brines. The inclusions within a given trapping plane have similar phase relationships; however, there are significant variations between inclusions in different healed fractures. Phase and chemical compositions of individual brine inclusions demonstrate significant compositional heterogeneity (in terms of absolute element concentrations and ratios) of high-temperature magmatic fluids accumulated in the miarolitic cavity. This finding suggests that fluids leaving a crystallizing magma may have variable initial compositions that are subsequently modified by reactions with the rocks while the fluid is in transit to a miarolitic cavity, as well as by processes in the cavity, such as mixing, crystallization, and boiling. The inferred chemical diversity and fractionation of granite-derived fluids at near-magmatic conditions imply that fluids entering a cooler hydrothermal system are extremely complex and their metallogenic signature may differ from that of related ore deposits.